Percepções da Problemática Ambiental pelos Agricultores Familiares do Sudoeste Paraense, Município de Pacajá (Sustainability in Debate, 2011)
Inserted study in the carried through actions of research-development in the regionof the Transamazônica, Southwest of Pará. The general objective is to identify thedecurrent environmental problems of the agricultural activity from the vision ofthe family farmers. Had been questionnaire used on the practical the 13 familiesand, 51 on the environmental perceptions. The environmental perceptions addaccumulated values, identities and interpretation on the relations and knowledge,conformed in strategies of social reproduction that nor always glimpse the ecologicalsupport, but yes material aspects and of exploration of the elements of the naturalway for satisfaction them necessities immediate human beings. The ambientquestion is perceived in the climatic changes to if evidencing drawn out periods ofdrought and greater heat sensation, and at the same time as concern imposed forthe pressure to the attendance to the environmental legislation. The family farmerscondition the changes in the practical of “slash-burn” to the support of thegovernments for implantation of productive alternatives.